Agricultural drones are taking off globally, saving farmers time and money - Belton, Ben; Baldiga, Leo (The Conversation, 2025)
Drones have become integrated into everyday life over the past decade – in sectors as diverse as entertainment, health care and construction. They have also begun to transform the way people grow food.